Analysis of Social Interaction Patterns in the Digital Age: The Impact of Social Media on Interpersonal Relationships - Djo Day, Yulyanti (Journal Social Humanity Perspective, 2023)
This research aims to analyze patterns of social interaction in the digital age, with a specific focus on the impact of social media usage on interpersonal relationships. The research methodology involved an online survey with participants from diverse backgrounds to collect data on the frequency of social interactions, types of shared content, and changes in the quality of interpersonal relationships. Descriptive and inferential statistical analyses were employed to identify common patterns and significant trends. The results indicate a shift in the dynamics of social interaction, where intensive use of social media can significantly influence the quality of interpersonal relationships, both positively and negatively, depending on the context and usage patterns. The implications of these findings for our understanding of social interaction in the digital era and the potential for changes in interpersonal behavior are highlighted in this study.